Improving the Pedagogical Competence of Senior Santri in Caring for Junior Santri to Prevent Violence and Bullying in Pesantren at Mojokerto - Yaqin , Ainul; Syarif, M.; Rozi, Syaikhu (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Acts of violence and bullying often occur in educational institutions, including Islamic boarding schools. This community service program is intended to improve the pedagogical competence of senior students in caring for junior students in Islamic boarding schools so that it can be expected to prevent violence and bullying. Prevention of acts of violence and bullying is sought by encouraging the strengthening of the use of cognitivism and humanism approaches, and minimizing the behaviorism approach. However, the use of these three approaches can be done proportionally and contextually. The program to increase the pedagogical competence of senior students should be carried out regularly or every year because the change of Islamic boarding school administrators which also takes place every year, automatically also changes the administrators. This program can also become a permanent RMI NU program which is more feasible in implementing the program than being carried out individually by Islamic boarding schools, while also having the advantage of being able to share the good practices of each Islamic boarding school.